Influence of timing of antenatal corticosteroid administration on morbidity of preterm neonates - Morhart, Patrick Daniel; Gärtner, Janis; Weiß, Christel; Stumpfe, Florian Matthias; Dammer, Ulf; Faschingbauer, Florian; Fahlbusch, Fabian B.; Beckmann, Matthias W.; Kehl, Sven (In vivo, 2022)
Background/Aim: We investigated the impact of the timing of antenatal corticosteroid (ACS) administration on the clinical outcome of preterm infants. Patients and Methods: Two hundred and fifty-five preterm infants between 28+0 and 34+0 weeks of gestation were retrospectively assigned to one of two groups: In the first group, ACS was given within 7 days before birth; the second group, did not receive ACS during that period. The primary outcome parameter was respiratory failure (defined by need for continuous positive airway pressure or mechanical ventilation) due to grade 1-4 respiratory distress syndrome (RDS). Secondary outcomes included the rates of intraventricular hemorrhage (IVH), periventricular leukomalacia, and necrotizing enterocolitis. Results: The rate of RDS was significantly higher in the no ACS group (40% vs. 62%, p=0.0009), especially of the more severe grades 24 (n=37 vs. n=48, p=0.0121). In addition, IVH (1% vs. 9%, p=0.0041) and neonatal infections (72% vs. 89%, p=0.0025) were significantly increased. Univariable and multivariable regression analyses showed a lower likelihood of RDS in the ACS group [odds ratio (OR)=0.295] in infants born closer to term (OR=0.907) and following preterm onset of labor (OR=0.495). Similarly, we observed a lower probability of IVH in the ACS group (OR=0.098), with a higher probability of occurrence of IVH in pre-eclampsia/HELLP syndrome (hemolysis, elevated liver enzyme levels, low platelet count) (OR=7.914). Conclusion: ACS treatment within the last 7 days before birth significantly reduced the risk of RDS and IVH in preterm. These data emphasize that the timing of ACS administration determines its success.
Gesehen am 08.01.2024